VARIATIONS OF DIRECTIVE SPEECH ACT IN TEMBANG DOLANAN - Daru Winarti; I Dewa Putu Wijana; Soepomo Poedjosoedarmo; Heddy Shri Ahimsa-Putra (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
This article discusses the directive speech acts contained in tembang dolanan. Using a pragmatic approach, particularly the framework of speech act theory, this article analyzes the different types of directive speech acts, the context which it embodies, and the level of decency. The data used in this research consisted of various tembang dolanan that contain directive statements. These data were analyzed using interpretation and inference by presenting it in the form of descriptive analysis. Descriptive analysis is meant to describe, systematically illustrating or elaborating the facts and relationships between phenomena. In the dolanan song, directive speech acts can be expressed directly or indirectly. Direct expression is conventionally used to rule, invite, and forward, while indirect expression is used when instead of by a command line, the intention is ruled by statement sentences, obligation-stating sentences, and questions. The use of direct speech acts generally does not have the value of politeness because they tend to still contain elements of coercion, have no effort to obscure the form of an order, and show the superiority of the speakers. On the other hand, the use of indirect speech acts seems to be an attempt to obscure the commandments to be more polite in the hope opponents would happily respond to commands.